Pengaruh Kepercayaan, Rating Pelanggan, dan Ulasan Pelanggan Terhadap Keputusan Pembelian Produk Parfum HMNS Pada E-commerce Shopee (Studi Kasus pada Mahasiswa Universitas Islam Malang) - Akbar, M. Ananda Fajar; Mawardi, Muhammad Cholid; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The aim of this study is to examine the individual and combined effects of trust, customer ratings, and customer reviews on consumers' purchasing decisions. The research population consists of students from the Islamic University of Malang who have previously purchased HMNS perfume products. A total of 80 respondents were selected as the sample, with the sample size determined using the Hair formula due to the unknown exact population size. This research employs a quantitative approach, and the data were analyzed using SPSS software. The findings indicate that trust, customer ratings, and customer reviews collectively have a significant influence on purchasing decisions. Furthermore, each of these variables also has a partial influence on consumer purchasing behavior. Keywords: Trust, Customer Ratings, Customer Reviews, Purchase Decisions